Diverse pathways generate microRNA-like RNAs and Dicer-independent small interfering RNAs in fungi - Lee, Heng-Chi (2010)
A variety of small RNAs, including the Dicer-dependent miRNAs and the Dicer-independent Piwi-interacting RNAs, associate with Argonaute family proteins to regulate gene expression in diverse cellular processes. These two species of small RNA have not been found in fungi. Here, by analyzing small RNA associated with the Neurospora Argonaute protein QDE-2, we show that diverse pathways generate miRNA-like small RNAs (milRNAs) and Dicer-independent small interfering RNAs (disiRNAs) in this filamentous fungus. Surprisingly, milRNAs are produced by at least four different mechanisms that use a distinct combination of factors, including Dicers, QDE-2, the exonuclease QIP and an RNAse III domain-containing protein MRPL3. In contrast, disiRNAs originate from loci producing overlapping sense and antisense transcripts, and do not require the known RNAi components for their production. Taken together, these results uncover several pathways for small RNA production in filamentous fungi, shedding light on the diversity and evolutionary origins of eukaryotic small RNAs.